1981
DOI: 10.1111/j.1399-0004.1981.tb00720.x
|View full text |Cite
|
Sign up to set email alerts
|

The identification of Y chromosome translocations following Distamycin A treatment

Abstract: Pretreatment of PHA‐stimulated lymphocyte cultures from normal males with 100 (μg/ml Distamycin A for the final 24 h of incubation led to a striking decondensation of the heterochromatic portion of the long arm of the Y chromosome. The despiralized region of Yq maintained its fluorescent properties in this altered morphologic state. Two cases of Y chromosome translocation (Y/22 and Y/X) were identified with this technique. A review of the literature revealed 62 similar cases in which the phenotypic‐karyotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Y/ autosome (Y;A) translocations are usually balanced and segregate in families with minimal effects on the phenotype [4][5][6]. On the other hand, unbalanced Y;A reciprocal translocations commonly present with infertility and azoospermia [7][8][9].…”
mentioning
confidence: 99%
“…Y/ autosome (Y;A) translocations are usually balanced and segregate in families with minimal effects on the phenotype [4][5][6]. On the other hand, unbalanced Y;A reciprocal translocations commonly present with infertility and azoospermia [7][8][9].…”
mentioning
confidence: 99%
“…15 is more often the recipient of Y translocation than other chromosomes. Reviewing the literature, Cohen et al (1981) summarized 62 Y-chromosome translocations, 26 cases of which were identified as a Y/15 transloca-tion. However, large 15p+ or 15s+ polymorphisms have occasionally been considered as the Y/15 translocation (Verma et al 1978, Spowart 1979.…”
mentioning
confidence: 99%